2017
DOI: 10.1111/jam.13634
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial isoeugenol coating on stainless steel and polyethylene surfaces prevents biofilm growth

Abstract: Aims: Pathogenic bacteria can spread between individuals or between food items via the surfaces they share. Limiting the survival of pathogens on surfaces, therefore, presents an opportunity to limit at least one route of how pathogens spread. In this study, we propose that a simple coating with the essential oil isoeugenol can be used to circumvent the problem of bacterial transfer via surfaces. Methods and Results: Two commonly used materials, stainless steel and polyethylene, were coated by physical adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…However, the maximum cell count after 48 h for S. aureus was about 2-Log lower than that of P. fluorescens . This result is in agreement with previous studies, which showed that S. aureus biofilms are usually less dense than P. fluorescens ones (Rossoni and Gaylarde, 2000; Nielsen et al, 2018). Nevertheless, S. aureus biofilms could cause cross-contamination via surfaces in the food field.…”
Section: Discussionsupporting
confidence: 94%
“…However, the maximum cell count after 48 h for S. aureus was about 2-Log lower than that of P. fluorescens . This result is in agreement with previous studies, which showed that S. aureus biofilms are usually less dense than P. fluorescens ones (Rossoni and Gaylarde, 2000; Nielsen et al, 2018). Nevertheless, S. aureus biofilms could cause cross-contamination via surfaces in the food field.…”
Section: Discussionsupporting
confidence: 94%
“…It is worth mentioning that attachment efficiency can be influenced by the characteristics of host surfaces, such as physicochemical interaction forces like hydrophobicity and electrostatic interactions (Gutierrez‐Pacheco et al., 2018; Hayat et al., 2018). A simple isoeugenol coating inhibits the biofilm formation of S. aureus , L. monocytogenes , and P. fluorescens through changing the hydrophobic properties of the surface (Nielsen et al., 2018). Similarly, Sc.…”
Section: Bacterial Biofilmmentioning
confidence: 99%
“…Infections associated with biofilm formation on the surface of implants, medical devices, catheters or food plates represent a major problem in surgical procedures, infection treatment, and recuperation. They constitute a serious risk for patients in the hospital environment [129,130]. Thus, limiting the survival of biofilm-embedded pathogens grants an opening to reduce the number of microbial infections [131].…”
Section: The Employment Of Atomic Force Microscopy In the Investigation Of Microbial Biofilmsmentioning
confidence: 99%